Community Structure And Attraction Of Reef Fish Associated With Artificial Reef In The Tahuna Bay - Makawaehe, Wenseslaus Fransiscus; Kusen, Janny D.; Manoppo, Lefrand; Bataragoa, Nego E.; Sambali, Haryani; Sumilat, Deiske A.; Mantiri, Rose O. S. E. (Sam Ratulangi University, 2021)
Community structure and interest of coral fish associated with artificial reefs in The Bay of Tahuna Sangihe Islands Regency is carried out in relation to increased coral fish production in Tahuna Bay. In addition to sandy waters and seagrass so that environmental engineering is pursued with artificial reefs. Artificial reefs are deployed in 5 locations with a depth of about 8 and underwater observations are carried out in data retrieval using the Underwater Visual Census (UVC) method. The data is processed to get a profile of the community structure of coral fish that can be associated with artificial reefs. The composition of coral fish species consists of target fish 9 families; 14 species, major fish 6 families; 7 species and fish indicator 1 family; 1 species. Indicator fish are generally eaters of the ends of young branch corals, branch corals have not grown in artificial reef structures. The diversity index (H') of the moderate category (+2.5) with a high, stable community, evenness (E) level or classified as a relatively high, uniformity (S) high. A low dominance index (C) indicates no species dominates. Mann-Whitney analysis about the level of fish interest to artificial reefs structure both in morning and evening showed no significant difference, while the highest acquisition of Important Values Indices of coral fish in the morning and evening, is Dascyllus trimaculatus by + 73,15. Generally, artificial reef indicates that the coral fish community was maximum developed yet, it was suspected that the coral fish community is still in the stage of adjustment or adaptation to the new environmental structure.Keywords: Community Structure; Artificial Reef; Associate Fishes; gulf TahunaAbstrakStruktur komunitas dan ketertarikan ikan karang yang berasosiasi dengan terumbu buatan di Teluk Tahuna Kabupaten Kepulauan Sangihe dilakukan dalam kaitan dengan peningkatan produksi ikan karang di Teluk Tahuna. Selain karena perairan berpasir dan lamun sehingga diupayakan suatu rekayasa lingkungan dengan penempatan terumbu buatan. Terumbu buatan diletakkan (deploy) di 5 lokasi dengan kedalaman sekitar 8 dan dilakukan pengamatan bawah air dan pengambilan data menggunakan metode Underwater Visual Census (UVC). Data diolah untuk mendapatkan profil struktur komunitas ikan-ikan karang yang dapat berasosiasi dengan terumbu buatan. Komposisi jenis ikan karang terdiri dari ikan target 9 family; 14 spesies, ikan mayor 6 family; 7 spesies dan ikan indikator 1 family; 1 spesies. Ikan indikator yang umumnya pemakan ujung karang cabang muda, karang cabang belum bertumbuh di struktur terumbu buatan. Indeks keanekaragaman (H’) kategori sedang (+ 2,5) dengan kemerataan (E) tergolong tinggi, komunitas stabil, keseragaman (S) tinggi. Indeks dominansi (C) rendah mengindikasikan tidak ada spesies mendominasi. Hasil Analisis Mann-Whitney terhadap tingkat ketertarikan ikan terhadap terumbu buatan baik pagi dan sore hari menunjukkan tidak ada perbedaan yang nyata artinya terumbu buatan mampu menarik ikan karang untuk berlindung dan mencari makan, sedangkan perolehan tertinggi Index Nilai Penting ikan karang saat pagi dan sore hari yaitu Dascyllus trimaculatus sebesar 72.04% dan 74.27% Secara umum menunjukkan terumbu buatan belum berkembang maksimal, di duga komunitas Ikan karang masih dalam tahap penyesuaian atau adaptasi dengan struktur terumbu buatan di lingkungan yang baru.Kata kunci: struktur komunitas; terumbu buatan; ikan asosiasi; teluk tahuna